Reconstruction of upper limb soft-tissue defects after sarcoma resection with free flaps: A systematic review. Issue 4 (April 2021) - Lucattelli, Elena; Lusetti, Irene Laura; Cipriani, Federico; Innocenti, Alessandro; De Santis, Giorgio; Innocenti, Marco
Summary: Background and Objectives: Upper limb preservation after soft tissue sarcoma (STS) surgical excision is now the accepted gold standard and it often requires reconstruction with free flaps. The purpose of this review is to summarize current literature on upper limb reconstruction with free flaps after STS resection. Methods: A systematic review was performed in July 2019 in PubMed and MedLine Ovid databases according to the PRISMA guidelines. Results: A total of 17 studies were included in the final analysis, with 132 patients. The most common diagnosis was Malignant Fibrous Histiocytoma. The most frequent timing of flap coverage was immediate. The success rate was almost always 100%. The length of follow-up was reported in 11 studies with a range of 2–187 months. The most commonly reported patient-centered outcome was the MSTS Score. Based on the evidence of the literature collected, we divided the upper limb into four parts (shoulder, elbow and arm, forearm and wrist, and hand) and described the most common and functional free flaps used for reconstruction after STS resection. Conclusions: Free flaps in the treatment of STS of the upper extremity have a good overall outcome, with a low postoperative complication rate. A wide array of free flaps is available for reconstruction, and the choice of flap is based on defect size, types of tissue required, postoperative functional goal, and surgeon preference. A greater degree of standardization is needed in the reporting of patient-centered outcomes to facilitate future comparative studies.